Formulation and Activity Test of Foot Spray from Sungkai Leaf Extract (PeronemacanescensJack) as an Antibacterial that Causes Foot Odor - Perawati, Santi; Wulandari, Aprilia; Aryani, Silvi Febri; Andani, Hasma (Riset Informasi Kesehatan, 2023)
Background : Sungkai is one of the medicinal plants used by the Suku Anak Dalam Tribe in Jambi to treat infectious diseases. Sungkai leaves contain secondary metabolites including alkaloids, flavonoids, terpenoids, steroids and tannins. Tannins and terpenoids are metabolites that have potential as antifungal , antibacterial and antiviral so they can be used in the cosmetics and pharmaceutical industries. Some bacterial infections can cause foot odor which can reduce a person's self-confidence. The aim of this research was to test Sungkai leaf extract which was formulated in foot spray dosage form to treat bacteria that cause foot odor, namely Staphylococcus epidermidis and Pseudomonas aeruginosa . Method : This research begins with the extraction stage of Sungkai leaves using the maceration method using 96% ethanol, then the resulting extract is continued with phytochemical screening testing, formulating the foot spray, and testing the antibacterial activity of foot spray. Antibacterial testing using by disc diffusion method, preparation of foot spray formulation using several series concentrations of Sungkai leaf extract there are 15% (F1), 20% (F2), and 25% (F3), and than followed by evaluation of foot spray formula includes organoleptic tests, pH tests , stability tests , irritation tests and liking tests. Results : Antibacterial activity of foot spray for both bacteria is in the medium category with average values of 7.29 and 7.11. The statistical test results at a p value of 0.05 show a significant difference between F0, FP, and F1. Conclusion : Based on the research that has been carried out, it can be concluded that foot preparation spray from Sungkai leaf extract is effective as an antibacterial especially for (F3) which contain an extract concentration of 25%. Keywords :Extract, sungkai leaves, foot spray , Peronema canescensJack, Pseudomonas aeruginosa And Staphylococcus epidermidis .